(untitled) (Journal of Humanitarian and Applied Sciences, 2026)
Hot desert regions are characterized by high levels of energy consumption in residential buildings, largely due to the heavy reliance on mechanical cooling systems to achieve indoor thermal comfort. This study aims to analyze the architectural characteristics of traditional houses in the old city of Ghadames, assess their level of thermal comfort, and examine energy consumption patterns in traditional dwellings. The study adopted a descriptive-analytical approach supported by a comparative method, focusing on the documentation and evaluation of the architectural and environmental characteristics of traditional houses in Ghadames. The findings indicate that traditional houses in Ghadames achieve remarkable indoor thermal stability compared to external temperatures. This performance is attributed to the thick walls and construction materials with high thermal mass. Moreover, the semi-enclosed spatial configuration, combined with internal courtyards and roof openings, facilitates natural air circulation, thereby contributing to thermal comfort without additional energy consumption. The study concludes with several recommendations, most notably the necessity of thoroughly examining traditional architectural strategies and the thermal performance of indigenous building materials, and integrating these principles into the planning and design of contemporary buildings and housing projects in hot arid regions.